2022
DOI: 10.1109/lsp.2022.3164850
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Angle Estimation for MIMO Systems via Redundancy Reduction Representation

Abstract: This paper proposes an efficient direction of departure (DOD) and direction of arrival (DOA) estimation method for multi-input multi-output (MIMO) systems. For uncorrelated scenarios, the redundancy of the covariance matrix is first exploited by establishing its concise representation through redundancy reduction, which transforms the original large-size covariance matrix into a smaller-size matrix without loss of useful angle information. Then, the resulting transformed matrix, which retains a salient structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…It is observed that in massive MIMO scenarios, the channel exhibits sparse multipath structure due to the limited scatterings. Thus, a virtual angular domain representation is applied to characterize the MIMO channel by fixed virtual receive and transmit directions [15]- [17]:…”
Section: A Channel Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…It is observed that in massive MIMO scenarios, the channel exhibits sparse multipath structure due to the limited scatterings. Thus, a virtual angular domain representation is applied to characterize the MIMO channel by fixed virtual receive and transmit directions [15]- [17]:…”
Section: A Channel Modelmentioning
confidence: 99%
“…The unrolled structure of the coarse estimation net in Network 1 is realized based on (19), where ΦT and α/q in (19) are replaced by the trainable weights W l e and θ l e in Step 3 of Network 1, respectively. Note that by considering largescale inter-frame sparsity, ( 8) is a typical l 2,1 minimization problem, thus δ α/q (•) can be directly extended to (13) and (17).…”
Section: B Coarse Estimation Netmentioning
confidence: 99%
See 3 more Smart Citations